PERAN SOSIAL PEREMPUAN DALAM AL-QUR`AN (Studi Tafsir Tematik Dengan Pendekatan Psikologi Agama) - Ubaidillah Ubaidillah (Kafa`ah: Journal of Gender Studies, 2020)
The social role of woman in religion contestation and community values tend to be discriminatory and it is not impartial for woman. This research is to elaborate al-Quran perspective in emphasizing the sociological and psychological women through a religious psychology approach. This research used thematic interpretation method by collecting certain verses that have closes meaning based on key term, such as; niswah ةْض/ًal Nisa ضاءٌال/al-unṡā ثىًاأل/al-mar‟u الوزأ/al-mar‟ الوزء/ al-imru‟ اإلهز dan al-mar‟ah الوزأة/ al-imra‟ah اإلهزأة ,.etc. The data analyses used psychology religion of Henry Nelson Wreman and Maturity Allport theory. The results of this research were: first, the function of woman's social role in al-Qur`an based on woman‟s dignity from various dimensions and social functions. Second, the evidence of woman‟s ability and maturity is, woman has social role‟s variety, like as wives, legal witnesses, political leaders, workers/employers, educators, and members of society. Third, the position of woman (based on socio-historically al-Qur`an) is on strategic function, like as in family, legal, politics, economi, da‟wah and socio-culturual system. Thus, discriminate and subordinated women are clearly contrary to the historical logic of the Qur'an.